Effect of the application technique on the colorimetric coordinates for a ceramic enamel (2020)
In ceramic tiles production processes for ornamental purposes, the industry uses enamel as raw materials that support the pigments that give coloration and tonal constancy in a glassy matrix. These parameters are of great interest in the acceptance of the final product by the consumer. Due to the increasing number of complaints related to variations in tone in ceramic enamel of the tiles produced by a ceramic company in northeastern Colombia, this work studied the enamel approval methodology's effect on the final tone of the ceramic pieces. A ceramic enamel was prepared and applied by the enameling pad technique on tiles manufactured by dry pressing. By applying the spectrophotocolorimetric technique, the colorimetric parameters were determined. The Tukey test's statistical results did not show statistical significance in the tile samples' tonal variation.